RAZVOJ LJUDSKIH RESURSA I INOVATIVNOST KAO DETERMINANTE UNAPREĐENJA GLOBALNE KONKURENTNOSTI PREDUZEĆA - Djuric, Dragana; Ristić, Jelena; Dragicevic, Predrag (International Journal of Economic Practice and Policy, 2022)
Human resources and innovation represent important elements of modern business processes. Business success depends primarily on human resources and business creativity in the current global business environment. In a competitive global economy, where other production factors (capital, technology, raw materials and information) can be copied, an organization’s human resources become the only source of permanent competitive benefit. In that sense, business entities in a globalized environment have to do business differently. Those radically new conditions require innovation and special quality of human resources, and new knowledge and skills of all actors in the economic arena. Such a business environment requires inventiveness and creativity of the persons managing knowledge and information, who create entrepreneurial atmosphere and create organizations based on innovation and teamwork work to overcome problems that arise from fast organizational change and integration of countries into international economic environment. The primary goal is to provide a better understanding of the roles of human resources and innovation in the performance improvement and competitiveness of global organizations and be of practical use regarding the perception of the importance of human resources management and innovation in modern business.